Geochemistry and Zircon U-Pb Chronology of West Kendewula Late Paleozoic A-Type Granites in the East Kunlun Orogenic Belt: Implications for Post-Collision Extension - Bang-Shi Dong; Wen-Qin Wang; Gen-Hou Wang; Pei-Lie Zhang; Peng-Sheng Li; Zhao-Lei Ding; Ze-Jun He; Pu Zhao; Jing-Qi Zhang; Chao Bo (Applied Sciences)
The Late Paleozoic granitoids widely distributed in the central section of the East Kunlun Orogenic Belt (EKOB) are responsible for the constraints on its post-collisional extensional processes. We report the whole-rock geochemical compositions, zircon U-Pb ages, and zircon Hf isotope data of granites in the western Kendewula area. The granites, dated between 413.7 Ma and 417.7 Ma, indicate emplacement during the Early Devonian period. The granite is characterized by high silicon content (72.45–78.96 wt%), high and alkali content (7.59–9.35 wt%), high 10,000 × Ga/Al values, and low Al2O3 (11.29–13.32 wt%), CaO (0.07–0.31 wt%), and MgO contents (0.16–0.94 wt%). The rocks exhibit enrichment in large-ion lithophile element (LILE) content and high-field-strength element (HFSE) content, in addition to strong losses, showing significant depletion in Ba, Sr, P and Eu. These geochemical characteristics correspond to A2-type granites. The values of Rb/N and Ba/La and the higher zircon saturation temperature (800~900 °C) indicate that the magma source is mainly crustal, with the participation of mantle materials, although limited. In addition, the zircon εHf(t) values (−4.3–3.69) also support this view. In summary, the A2-type granite exposed in the western Kendewula region formed against a post-collisional extensional setting background, suggesting that the Southern Kunlun Terrane (SKT) entered a post-orogenic extensional phase in the evolution stage since the Early Devonian. The upwelling of the asthenospheric mantle of the crust, triggered by crustal detachment and partial melting, likely contributed to the flare-up of A2-type granite during this period. By studying the nature of granite produced during orogeny, the evolution process of the formation of orogenic belts is discussed, and our understanding of orogenic is enhanced.